KINERJA KARYAWAN: PROSES REKRUTMEN DAN SELEKSI PADA SMARTCLUB TRADER WHOLESALE - Sri Nilawati; Bambang Suhartoyo; Masturo Masturo; Vinthya Dwi Darmawanti (Jurnal Comparative: Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the effect of the recruitment and selection process on employee performance at Smartclub Trader Wholesale Metropolis. To find out which factors have a more dominant influence on employee performance at Smartclub Trader Wholesale Metropolis. The subjects in this study were 58 employees in the HRD section at Smartclub Trader Wholesale Metropolis. The data analysis method used in this study uses the help of a computerized system (SPSS Computer Program version. 23) to test whether there is an influence between the recruitment and selection process on employee performance. The data collection technique is the questionnaire method, while the analysis technique used is multiple regression analysis with the t test and F test. Partial calculation results are obtained for the recruitment process t count 6.512 > t table 2.00404 and selection t count 2.341 > t table 2, 00404, it can be concluded that the process of recruitment and selection has a partial effect on employee performance. While the simultaneous test results obtained F count 21.977 > F table 3.16. This means that the recruitment and selection processes jointly affect the performance of employees at Smartclub Trader Wholesale Metropolis